The relationship of Total Quality Management (TQM) upon employees' role conflict in Akademi Laut Malaysia (ALAM) Sdn. Bhd. / Azatulaein Jamaluddin - Jamaluddin, Azatulaein (Faculty of Business and Management, 2013)
Total Quality Management (TQM) is process to arrangmg a constant enhancement for presentation of both manufacturing and service organization while role conflict is communal psychological stressors that have been adjusted in the early level of study that connected to work stress. The purpose of this research was to examine the relationship of TQM practices with employees' role conflict in Akademi Laut Malaysia (ALAM) Sdn. Bhd. Melaka. The scope of this research study focused on the middle and lower employees in ALAM organization. The instrument that was used to gather data is by distributing questionnaires. The questionnaires were distributed to 118 respondents at ALAM, Melaka. The findings indicated that customer focus and information analysis practices were observed to significant in order to reduce role conflict among ALAM's employees and descriptive statistic showed employees considered neutral for role conflict variables. Therefore, it was recommended that specific training must be provided, policies and procedures in organization must be standardized and good relationship with stakeholder must be maintained to make sure others TQM practice such as human resource focus, strategic planning and process management will be able to reduce role conflict among employees.